The relationship between trait mindfulness and inclusive education attitudes of primary school teachers: a multiple mediating model - Huang, Fenxia (Frontiers in Psychology, 2023)
Objective: This study aims to explore the impact of primary school teachers' empathy and efficacy for inclusive practice on the relationship between trait mindfulness and inclusive educational attitudes. Methods: A total of 606 primary school teachers were tested using the Five Facet Mindfulness Questionnaire, Interpersonal Response Index Scale, Teacher Self-efficacy for Inclusive Practice Scale, and Teachers' Multidimensional Attitudes toward Inclusive Education Scale.Results: Primary school teachers' trait mindfulness is significantly positively correlated with inclusive educational attitudes. Primary school teachers' trait mindfulness has an indirect impact on inclusive education attitudes through empathy, and primary school teachers' trait mindfulness has an indirect impact on inclusive education attitudes through teacher efficacy for inclusive practice. In addition, empathy and teacher efficacy for inclusive practice play a sequential mediating role between primary school teachers' trait mindfulness and inclusive education attitudes. Conclusion: This empirical study reveals that empathy and efficacy for inclusive practice play a sequential mediating role between primary school teachers' trait mindfulness and inclusive education attitudes. On one hand, this research contributes to enriching the outcomes in the field of inclusive education for primary school teachers, providing a theoretical foundation for the study of their inclusive education attitudes. On the other hand, the study offers a detailed explanation of the psychological mechanisms behind the impact of mindfulness traits on the inclusive education attitude of primary school teachers, guiding schools in implementing mindfulness-based intervention programs.